Impact of Biochar on Growth and Productivity of Broccoli in Coastal areas (Journal of the Bangladesh Agricultural University, 2024)
Agricultural practices in coastal regions face significant challenges due to poor soil quality and limited nutrient availability. This study investigates the impact of maize straw biochar on the growth and yield of broccoli (Brassica oleracea) in Bangladesh's coastal region, aiming to improve crop performance while reducing dependence on conventional fertilizers. Biochar is expected to enhance soil quality by improving water retention, nutrient availability and microbial activity, making it a promising soil amendment in challenging agricultural conditions. From December 2021 to March 2022, five biochar treatments (0, 2, 4, 6 and 8 tons/ha) were utilized in the field experiment. Each treatment was duplicated three times using a Randomized Complete Block Design (RCBD). The results suggested that biochar greatly enhanced a number of growth parameters, such as leaf length, leaf breadth, dry curd weight and chlorophyll content. The highest yield (5.35 tons/ha) and primary curd weight were achieved with 8 tons/ha of biochar. However, no significant differences were observed in plant height, leaf number or primary curd diameter across treatments. These findings suggest that biochar, particularly at 8 tons/ha, is a promising soil amendment for enhancing broccoli productivity in coastal regions. Further research is recommended to explore the long-term impacts of biochar and its interactions with environmental factors and soil properties to optimize its use in agricultural systems.J Bangladesh Agril Univ 22(4): 432-442, 2024